2015
DOI: 10.1007/s10103-015-1723-8
|View full text |Cite
|
Sign up to set email alerts
|

Time response of increases in ATP and muscle resistance to fatigue after low-level laser (light) therapy (LLLT) in mice

Abstract: Recently, low-level laser (light) therapy has been used to increase muscle performance in intense exercises. However, there is a lack of understanding of the time response of muscles to light therapy. The first purpose of this study was to determine the time response for light-emitting diode therapy (LEDT)-mediated increase in adenosine triphosphate (ATP) in the soleus and gastrocnemius muscles in mice. Second purpose was to test whether LEDT can increase the resistance of muscles to fatigue during intense exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
3
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 33 publications
2
48
3
6
Order By: Relevance
“…The authors demonstrating that phototherapy reduces lactate levels in the circulation due to increased local microcirculation and consequently increased in oxygen supply. As a consequence, there is an improvement in muscle fatigue, faster recovery of muscle damage and improved performance, both in humans and animals [34][35][36]38]. In this context, our research group demonstrated in exogenous obese rats that the association of low-level laser therapy (LLLT) plus moderate swimming training promoted decrease in adipocyte area and increase in the energetic demand and in the mitochondrial oxidative capacity besides greater workload (data not published).…”
Section: Discussionmentioning
confidence: 99%
“…The authors demonstrating that phototherapy reduces lactate levels in the circulation due to increased local microcirculation and consequently increased in oxygen supply. As a consequence, there is an improvement in muscle fatigue, faster recovery of muscle damage and improved performance, both in humans and animals [34][35][36]38]. In this context, our research group demonstrated in exogenous obese rats that the association of low-level laser therapy (LLLT) plus moderate swimming training promoted decrease in adipocyte area and increase in the energetic demand and in the mitochondrial oxidative capacity besides greater workload (data not published).…”
Section: Discussionmentioning
confidence: 99%
“…LLLT can also accelerate cellular metabolic processes and increase synthesis of ATP [8] with an anti-inflammatory effect (release of inflammatory mediators, stimulation of microcirculation, absorption of exudates, and interference in the synthesis of prostaglandins) [12,13]. Research corroborates the influence of LLLT in relation to the recruitment of muscle fibers and the torque peak, in addition to delaying development of muscle fatigue, which contributes to a greater musculoskeletal performance [6,[14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 83%
“…Moreover, increases in ATP content in muscle cells and tissue, fatigue resistance, strength, oxidative stress defense, prevention of muscle damage, and improvement of the kinetics of oxygen consumption 7,8,10,12,17,4143 can also be elicited when phototherapy is applied to muscles before a single bout of exercise (muscular preconditioning). However, it seems there is an optimum time to apply phototherapy when used in a muscular preconditioning regimen as judged by increases in ATP synthesis in muscles, mitochondrial metabolism, and fatigue resistance that are maximal at some hours after light application.…”
Section: Discussionmentioning
confidence: 99%
“…However, it seems there is an optimum time to apply phototherapy when used in a muscular preconditioning regimen as judged by increases in ATP synthesis in muscles, mitochondrial metabolism, and fatigue resistance that are maximal at some hours after light application. 8,17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation